Solid‐phase extraction techniques based on nanomaterials for mycotoxin analysis: An overview for food and agricultural products. Issue 13 (11th April 2022) - Tang, Zhentao; Liu, Fei; Fang, Fang; Ding, Xuelu; Han, Qingrong; Tan, Yuzhu; Peng, Cheng
Abstract : Mycotoxin contamination is a globally concerned problem for food and agricultural products since it may directly or indirectly induce severe threats to human health. Sensitive and selective screening is an efficient strategy to prevent or reduce human and animal exposure to mycotoxins. However, enormous challenges exist in the determination of mycotoxins, arising from complex sample matrices, trace‐level analytes, and the co‐occurrence of diverse mycotoxins. Appropriate sample preparation is essential to isolate, purify, and enrich mycotoxins from complicated matrices, thus decreasing sample matrix effects and lowering detection limits. With the cross‐disciplinary development, new solid‐phase extraction strategies have been exploited and integrated with nanotechnology to meet the challenges of mycotoxin analysis. This review summarizes the advance and progress of solid‐phase extraction techniques as the methodological solutions for mycotoxin analysis. Emphases are paid on nanomaterials fabricated as trapping media of solid‐phase extraction techniques, including carbonaceous nanoparticles, metal/metal oxide‐based nanoparticles, and nanoporous materials. Advantages and limitations are discussed, along with the potential prospects.